The Relationship Between Physical Activity and Mental Well-being: An Empirical and Theoretical Study - Munthe, Irwan Salomo; Rendi, Rendi; Meri, Meri; Setiawan, Muhammad Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to analyze the relationship between physical activity and mental well-being among students of the Sports Science Department at Universitas Singaperbangsa Karawang (UNSIKA). The research employed a quantitative approach with a correlational design, involving 100 respondents selected through stratified random sampling. Data were collected using the International Physical Activity Questionnaire (IPAQ) to measure physical activity levels and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) to assess mental well-being. The findings revealed a significant positive correlation (r = 0.62, p < 0.01) between physical activity and mental well-being. Students with higher physical activity levels demonstrated better mental well-being, characterized by optimism, energy, and the ability to manage stress. Conversely, those with lower physical activity levels reported reduced mental well-being, including symptoms of anxiety and depression. Furthermore, the study highlighted the negative impact of prolonged sitting (over 5 hours daily) on mental well-being, emphasizing the importance of integrating physical activity into daily routines. The study concludes that physical activity plays a vital role in enhancing mental well-being among university students. It recommends increased participation in moderate to vigorous physical activities and reduced sedentary behaviour to improve overall quality of life. Future research should explore additional variables influencing mental well-being to provide a more comprehensive understanding of the topic.